Elastomers 2017
DOI: 10.5772/intechopen.68384
|View full text |Cite
|
Sign up to set email alerts
|

Nitrile Elastomer/LDH Composites with Varying Mg/Al Ratio, Curing, Nanoparticles Dispersion and Mechanical Properties

Abstract: Layered double hydroxides (LDHs) tend to be a promising material in the field of polymer nanocomposites because it possesses unique chemical and structural properties. The novelty of layered double hydroxides (LDHs) comparing to other conventional fillers is connected with possibility of surface functionalization by introduction of various organic species into an interlayer area. Organic modifiers could act not only as intercalation promoters but also have additional functions such as UV stabilizers, anti-agin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…This fact is attributed to a stronger filler-filler interactions and larger surface area of both MG5 and MG30 fillers. According to our previous studies [14], the surface area of MG63 and MG70 (Mg-rich fillers) was much lower (MG63 −200 m 2 ˑg −1 , MG70 −196 m 2 ˑg −1 ) than MG5 and MG30 (MG5 250 m 2 ˑg −1 , MG30 276 m 2 ˑg), as measured after activation (calcination) at 550 °C for 3 h. Others studies showed [30] that also before calcination MG63 and MG70 fillers exhibited lower surface area comparing to MG30. The increase in this parameter resulted in the enhancement of the interphase contact between the solid surface and elastomer and thus had impact on the flow behavior at whole range of shear rate.…”
Section: Analysis Of the Complex Viscosity Of The Materialsmentioning
confidence: 96%
See 4 more Smart Citations
“…This fact is attributed to a stronger filler-filler interactions and larger surface area of both MG5 and MG30 fillers. According to our previous studies [14], the surface area of MG63 and MG70 (Mg-rich fillers) was much lower (MG63 −200 m 2 ˑg −1 , MG70 −196 m 2 ˑg −1 ) than MG5 and MG30 (MG5 250 m 2 ˑg −1 , MG30 276 m 2 ˑg), as measured after activation (calcination) at 550 °C for 3 h. Others studies showed [30] that also before calcination MG63 and MG70 fillers exhibited lower surface area comparing to MG30. The increase in this parameter resulted in the enhancement of the interphase contact between the solid surface and elastomer and thus had impact on the flow behavior at whole range of shear rate.…”
Section: Analysis Of the Complex Viscosity Of The Materialsmentioning
confidence: 96%
“…The increment of elastic torque ΔS ′ defined as ΔS ′ = S ′ max -S ′ min , where S ′ max -maximum elastic torque, S ′ min -minimum elastic torque, was calculated based on the curing curves. The range of temperatures studied and vulcanization parameters were chosen based on our previous studies [14] and based on the DSC measurements indicating the range of curing temperatures for every type of Mg-Al-LDHs-XNBR formulas. From rheometric RPA experimental data, the cure rate α at time t was calculated using Eq.…”
Section: Kinetic Of Curingmentioning
confidence: 99%
See 3 more Smart Citations